Emissions mitigation in New Zealand dairy farming : a delphi study - Van Ausdal, William (2013)
Dairy farming in New Zealand is responsible for approximately 18% of total New Zealand emissions (Ministry for the Environment, 2008). Reducing dairy farming’s share of emissions can therefore significantly reduce the nation’s emissions profile. There are a variety of methods that offer potential to mitigate dairy related emissions. This Delphi study examined the expert opinions of a select group of New Zealand agricultural science professionals regarding the feasibility, effectiveness and affordability of practices and technologies to assist farmers in reducing the emissions of their on-farm operations. Assessing mitigation practices and technologies is an important step in developing effective environmental policy and addressing New Zealand’s agricultural emissions. Interestingly, promoting subsidies for operational and technological change as an alternative to emissions tax was considered more effective as an emissions mitigation policy at the farm level. Farm management was recommended for subsidy over technology solutions and it was seen to hold the greatest potential in reducing emissions. The techniques that were deemed most effective to reduce nitrous oxide included nitrification inhibitors, nutrient budgeting and winter management. When considering economic viability, winter management and nutrient budgeting were viewed most favourably. The methods with the highest potential to reduce methane emissions (or increase biological efficiency) included genetic selection and feed supplements. A further focus on feed revealed that mixed crops and starch were highly effective supplements. In terms of economic viability, feed supplements and genetic selection were viewed most favourable. Additional research should prioritise practical options (by cost) to understand whether scientifically tested options match the profitability requirements of the farming community. This research would prove valuable to policymakers to further understand the potential economic and environmental implications of mitigation strategies.